Interpreting conversion in antiquity (and beyond) - Jacobs, Andrew S. (Religion compass, 2021)
This essay explores the persistent scholarly desires and motivations that structure the historical study of conversion in religious studies. Most “conversion studies” take a phenomenological approach, which acknowledges the diverse processes, contexts, and meanings of conversion but nonetheless sees the phenomenon as a way to access the contours of global religion. Phenomenology of conversion reveals a desire for bounded religions arranged in a comparable system, “religion.” A hermeneutical approach to conversion does not seek to access a stable phenomenon but asks why conversion as a discourse is deployed. This form of narrative interpretation can open up new possibilities in what we think the study of religion can, and should, do. The specific examples of Jewish conversion to Christianity in late antiquity act as case studies.